Tourism marketspace on the Internet. - Chin, Heng Ee. (2009)
According to WTTC, Travel & Tourism is the world's largest industry and generator of quality jobs. In Singapore, its many economic spin-offs on related industries have probably made it the most important sector of Singapore's economy. Singapore now faces growing competition from its regional neighbours. Coupled with its inherent lack of natural resources, Singapore must critically enhance its attractiveness as a tourist destination and create new room for the growth of the local tourism industry if it wants to remain in business.